Antecedent and Consequence Analysis of Investor Behavior Variables in Retail Shares on The Indonesian Stock Exchange - Wisnu Yuwono; Yosep Deki Antalius; Mukdad Ibrahim; Edy Yulianto Putra; Dewi Khornida Marheni (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The Indonesia Stock Exchange (IDX) over the last four years (2019-2022) shows an average increase in the number of investors of 60.91%. However, this did not significantly impact market capitalization, which grew 9.86%, and the average growth of the Jakarta Composite Index, which was only 3.03% over the last four years. The data is very interesting to analyze further regarding investor behavior in investing in the stock market.Purpose: This research aims to analyze the influence of financial knowledge, investment experience, information media, and social interaction on retail investor behavior and the influence of retail investor behavior on investment decisions. Design/methodology/approach: Research data was taken from 292 stock investors, using a purposive sampling technique. Data processing and analysis use Structural Equation Modeling (SEM) with Smart PLS 3.2.9. Finding/Result: The research results show that financial knowledge and information media do not have a significant effect on retail investor behavior. Investment experience and social interaction have a positive and significant effect on retail investor behavior. Retail investor behavior has a significant influence on investment decisions. Other findings show that investor behavior cannot mediate the relationship between the variables of financial knowledge, investment experience, information media, and social interaction on investment decisions. Conclusion: Financial knowledge and media information are no longer the basis of investor behavior, both of which have been replaced by more subjective factors, namely investment experience and social interaction. Investor behavior is also unable to mediate the relationship between the four variables and investment decisions.Originality/value (State of the art): This study is to investigates the relationship between fundamental aspects and subjective aspects on retail investor behavior and the influence of investor behavior on investment decisions, so that the authors develop new models in research. Fundamental aspects are no longer something interesting for investors because of less credible information, so they prefer to use experience and social interaction. The role of company managers is to provide more credible information through financial reports, and the need for information media management in encourage investors to invest. Keywords: investment decision, retail investor behavior, financial knowledge, investment experience, media information, social interaction